(untitled) (Research, Society and Development, 2022)
Lean Manufacturing methods are used by industries that seek to improve their competitiveness through flexibility, cost reduction, product quality improvements and customer satisfaction. Still, the level of complexity and demand in the manufacturing industry is rapidly expanding, intensifying organizational problems. Industry 4.0 systematically employs state-of-the-art technological solutions, unlike Lean Manufacturing, which is firmly based on the human factor. With a qualitative approach, this study aims to explore the synergistic aspects between Lean Manufacturing and Industry 4.0 in an integrative review. The searches were carried out in the following databases: Web of Science, Scopus, Science Direct and IEEE, totaling 552 articles, of which 19 were selected after applying the inclusion and exclusion criteria. The results show that the technologies that stood out the most in Industry 4.0 with Lean Manufacturing are the Internet of Things, Big Data and Cyber-Physical Systems, making processes faster and more efficient when integrated. A theme identified in two studies was the presence of the Lean leader, who has Lean management skills and is recognized as a critical factor for the implementation of Industry 4.0, as it requires a broad view of the organizational process and the application of Lean tools.